Analisis Kinerja Instansi Pemerintahan Di Kantor Sektretariat DPRD Provinsi Kepualauan Riau - Rinah, Sri Ambar; Suryanti Nengsih, Neng; Effendi, Desrian; Dwiniati, Dwiniati (STISIPOL Raja Haji, 2024)
Employees are required to be able to carry out performance in accordance with their capacity, in the performance reports of government agencies it has been summarized in such a way as to be submitted to the governor for evaluation and also checked whether it has gone well or not. According to the existing phenomenon, there are still budgets that have not been fully realized this is due to the lack of accurate reporting to make a report that will see its realization. A weak reporting system will have an impact on the reports that have been made by the LAKIP team. The purpose of this reporting system is to find out whether the preparation of the LAKIP can run well and also to correct whether there are still errors in the preparation. The purpose of the study was to analyze the performance of government agencies at the DPRD Secretariat of the Riau Islands Province. In this study, the theory used is the theory of opinion. The operational concept of Sony Yuwono, et al (2005: 36). The population in the study amounted to 5 people, the data analysis used in this study was a qualitative descriptive data analysis technique. Based on the results of the study, it can be concluded that the Performance of Government Agencies in the Riau Islands Provincial DPRD Secretariat Office has been going well but is still not optimal, this can be seen from the results of the research. access by the public, but if you look at there is a website, https://dprd.kepriprov.go.id/ where if you look at the information provided should have been able to be obtained by the community because it has been presented but in reality, the content of the website is very limited, even the information section is empty, information is still very minimal, even profiles, leaders, and so on can not be accessed, then there is another website that is used, namely https://ppid.kepriprov.go.id/informationpublik but it is also very limited, for the Riau Islands Provincial DPRD, no information is found whatever. Suggestions that can be conveyed is the need for increased disclosure of information that is easily accessible by the public. There needs to be an increase in performance in seeing the needs of the public or the community.